2021
DOI: 10.1016/j.imu.2021.100725
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel transmembrane Protease Serine Type 2 drug candidates for COVID-19 using computational studies

Abstract: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) emergence has resulted in a global health crisis. As a consequence, discovering an effective therapy that saves lives and slows the spread of the pandemic is a global concern currently. In silico drug repurposing is highly regarded as a precise computational method for obtaining fast and reliable results. Transmembrane serine-type 2 (TMPRSS2) is a SARS CoV-2 enzyme that is essential for viral fusion with the host cell. Inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…The active site of the TMPRSS2 showed hydrogen bonding with the residues SER460, ASN418, LYN342, THR341, PO4501, GLU299, GLY464, ASP435, ASN343, ASP345, LYS342, TYR337 which played a significant role in binding with the ligands as analyzed from the binding interaction analysis. Similar results with different molecules were shown in different computational and experimental studies [ 36 , 46 , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] ]. In our previous work, GLU299, GLY464, ASP435, PO4501, SER460, SER436, LYS342, ASN418, LYS340, TRP461, PO4 501, THR341 showed H-bond with the ligand [ 46 , 64 ].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The active site of the TMPRSS2 showed hydrogen bonding with the residues SER460, ASN418, LYN342, THR341, PO4501, GLU299, GLY464, ASP435, ASN343, ASP345, LYS342, TYR337 which played a significant role in binding with the ligands as analyzed from the binding interaction analysis. Similar results with different molecules were shown in different computational and experimental studies [ 36 , 46 , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] ]. In our previous work, GLU299, GLY464, ASP435, PO4501, SER460, SER436, LYS342, ASN418, LYS340, TRP461, PO4 501, THR341 showed H-bond with the ligand [ 46 , 64 ].…”
Section: Discussionsupporting
confidence: 88%
“…Similar results with different molecules were shown in different computational and experimental studies [ 36 , 46 , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] ]. In our previous work, GLU299, GLY464, ASP435, PO4501, SER460, SER436, LYS342, ASN418, LYS340, TRP461, PO4 501, THR341 showed H-bond with the ligand [ 46 , 64 ]. In a work done by Idris M. et al group LYN342, Asp435, SER460, SER436, TRP461, GLY464, LYN342 showed H-bond with the ligand [ 69 ] also Asp435, SER436, TRP461, GLY464, GLU 299, LYS342 showed the same interactions in a work conducted by Kumar V. et al group [ 68 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The TMPRSS2 enzyme of SARS-CoV-2 is also considered a target for the suppression of virus infection. Elbadwi et al applied structure-based virtual screening to search for drugs with the potential to target SARS-CoV-2 TMPRSS2, and identified 5 commercially available drugs amikacin, isepamicin, butikacin, lividomycin, and paromomycin, possibly having inhibitory abilities against the TMPRSS2 enzyme [ 58 ]. Hamdy et al applied an iterated virtual screening method to re-screened M pro effective compounds against a TMPRSS2 structure (PDB: 2OQ5) using molecular docking [ 59 ].…”
Section: R Epurposed T Herapeutic ...mentioning
confidence: 99%